Heterogeneous air pollution controls its correlation to urban heat island: A satellite perspective. Issue 12 (15th June 2022) - Ding, Ying; Feng, Huihui; Zou, Bin; Nie, Yunfeng
Highlights: Correlation between air pollution and urban heat island was examined. Air pollution mitigates regional SUHI by reducing surface solar radiation. Air pollution difference in urban and rural aggravates spatial variability of SUHI. Air pollution impacts on SUHI depends on spatial heterogeneity of the pollution. Abstract: Air pollution and surface urban heat island (SUHI) interacts through several physicochemical mechanisms. However, the correlation varies under different climatic and geographic conditions. This study evaluates the contribution of air pollution on SUHI and their correlation over Changsha-Zhuzhou-Xiangtan urban agglomeration (CZT) using satellite observations and statistical analysis. Results show that aerosol negatively correlated to SUHI under severe air pollution, while positively correlated under the relatively clean air condition. On the other hand, the difference of air pollution between urban and other areas positively correlates to the SUHI, indicating that the worsening air pollution in urban area might aggravate the adverse effects of the urban heatwave. The net weakening or aggravating impacts of air pollution to SUHI strongly depends on the heterogeneity of the air pollution over the urban and rural regions. Estimation of relative contribution indicates that SUHI variation was mainly affected by cloud fraction and relative humidity, and the contribution of aerosol was about 9.48–17.11% under different meteorological conditions. Clarification of the correlation helps to support the land planning and environment management under the rapid urbanization.